Periodontal inflammation and distinct inflammatory profiles in saliva and gingival crevicular fluid compared with serum and joints in rheumatoid arthritis patients. Issue 10 (16th March 2021) - Arvikar, Sheila L.; Hasturk, Hatice; Strle, Klemen; Stephens, Danielle; Bolster, Marcy B.; Collier, Deborah S.; Kantarci, Alpdogan; Steere, Allen C.
Abstract: Background: The association of periodontitis and Porphyromonas gingivalis ( Pg ) with rheumatoid arthritis (RA) is incompletely understood. To gain further insights, we evaluated periodontal status, oral, serum and joint inflammatory profiles, and Pg biomarkers in RA patients. Methods: In this cross‐sectional study, we evaluated 33 patients with predominantly untreated new‐onset RA, 20 healthy individuals (HIs), and 20 non‐RA chronic periodontitis patients. Thirteen mediators (IFN‐γ, IL‐10, IL‐17A, IL‐6, IL‐8, CXCL10, TNF‐α, CXCL13, IL‐23, MMP‐1, MMP‐3, MMP‐8, MMP‐9) were measured in serum, synovial fluid, saliva and gingival crevicular fluid (GCF) by multiplex immunoassay. Serum Pg IgG antibodies and subgingival Pg DNA were determined. Results: Most RA patients (91%) received routine dental care; only one currently smoked. Ten (30.3%) had periodontal health, 13 (39.4%) had gingivitis, and 10 (30.3%) had periodontitis. Th1 and innate immune responses predominated in serum. Many mediators were concentrated in joints, particularly IL‐6, IL‐8, and CXCL10. However, salivary and GCF profiles were more restricted, emphasizing neutrophilic inflammation (IL‐8, MMP‐8) and MMP‐9. Compared with HI, most RA patients, regardless of periodontal status, had significantly elevated oral fluid levels of these mediators, with suppression of GCF IL‐10, a pattern similar to non‐RA periodontitis patients. Pg antibodies or DNA however were primarily associated with clinical periodontitis. Conclusions: Despite routine dental care, RA patients often had inflammation in oral fluids, but inflammatory profiles differed from serum and joints. Neutrophilic inflammatory profiles in oral fluids, regardless of periodontal status, suggests that gingival tissues are a common, and often unrecognized, site of extra‐articular inflammation in RA.